2021
DOI: 10.3390/en14154400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Temperature on the Magnetic and Energetic Properties of Soft Magnetic Composite Materials

Abstract: In recent years, innovative magnetic materials have been introduced in the field of electrical machines. In the ambit of soft magnetic materials, laminated steels guarantee good robustness and high magnetic performance but, in some high-frequency applications, can be replaced by Soft Magnetic Composite (SMC) materials. SMC materials allow us to reduce the eddy currents and to design innovative 3D magnetic circuits. In general, SMCs are characterized at room temperature, but as electrical machines operate at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The authors concluded that the effective permeability of the Fe-6.5 Si/nano-MnZn ferrites SMCs first increases and then decreases with an increase in nano-MnZn ferrite content. The optimum comprehensive performances are obtained with 2 wt% MnZn ferrites (optimum magnetic performance for Fe-6.5 Si/nano-MnZn ferrite SMCs annealed at 400 • C) [20].…”
Section: Simulation Of Magnetic Properties Of Composites Based On Mag...mentioning
confidence: 99%
“…The authors concluded that the effective permeability of the Fe-6.5 Si/nano-MnZn ferrites SMCs first increases and then decreases with an increase in nano-MnZn ferrite content. The optimum comprehensive performances are obtained with 2 wt% MnZn ferrites (optimum magnetic performance for Fe-6.5 Si/nano-MnZn ferrite SMCs annealed at 400 • C) [20].…”
Section: Simulation Of Magnetic Properties Of Composites Based On Mag...mentioning
confidence: 99%
“…[4] Soft magnetic materials have been widely used due to their high saturation magnetization, low coercivity, and high permeability. [5,6] GMI effect is the changing of the impedance experienced by an AC current flowing through a magnetic material with external DC magnetic field. [7] Asymmetric giant magneto-impedance (AGMI) is another form of GMI discovered in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the efficiency and conveniency requirements of future energy-conversion devices, the miniaturization and high frequency of these devices have become an inevitable trend [1,2]. Soft magnetic composites (SMCs), consisting of magnetic metal powders and an insulating layer, exhibit the advantages of high saturation magnetization, high electrical resistivity, high permeability, low core loss, and flexible shape [3][4][5][6][7][8][9]. These advantages meet all the requirements of future overlooked.…”
Section: Introductionmentioning
confidence: 99%